Morsel - Keane, Carter (Nightfire, 2026)
"Carter Keane's Morsel is a delicious folk horror debut about learning to bite back when the world is determined to eat you alive. Lou did what the children of parents with backbreaking, poorly paying jobs are supposed to do: pulled up her bootstraps, went to college, and got an office gig with coworkers who won't stop talking about their multilevel marketing scheme disguised as self-betterment. When Lou accepts a property appraisal assignment in the rural hills of Ohio, she knows it's her last chance to save her job and keep making rent. But she quickly finds herself stranded in the middle of nowhere with a sabotaged truck, her dog, and someone--or something--stalking her through the ancient Appalachian woods. If she can't escape the woods in time, she'll see firsthand that her job isn't the only thing that wants to eat her alive. Morsel is The Blair Witch Project meets The Ritual, with a generous helping of The Menu, perfect for fans of T. Kingfisher, Cassandra Khaw, and Paul Tremblay"-- Provided by publisher.